Predictors of hydrodynamic technical and tactical training system for blind and partially sighted Paralympic swimmers - Vinokourov, L.V.; Mosunov, D.F.; Tveryakov, I.L. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze and test benefits of a new individual technical abnormalities sensitive technical and tactical training system for blind and partially sighted swimming elite. Methods and structure of the study. We made a qualifying analysis of the surface/ underwater swimming technique videos to rate every phase in the Paralympic swimmers’ techniques in every style, with occasional applications of skin-fixed LED indicators [1]; plus an expert survey and practical experience analyses by specific topics on a sample of the blind and partially sighted elite (Masters of Sports, World Class Masters of Sports, Honored Masters of Sports) coaches Results and conclusion. The study found specific and typical individual technical abnormalities in the elite blind and partially sighted sample, with their identification and classification showing the coach and athlete the individual technical and tactical training service and swimming technique improvement needs and priorities. We believe that the individual technical abnormalities should no more be perceived as swimming technique errors in the blind and partially sighted swimming sport as they are necessitated by the individual blind-and-partially-sighted-related primary locomotion patterns. We analyze herein the individual technical abnormalities classes and differences with practical correction options.